Assessing the Effect of Liquidity Management on the Performance Of Deposit Money Banks In Nigeria. - Nzotta, Samuel Mbadike; Atuonwu, Obiageri Eunice (Advances in Social Sciences Research Journal, 2020)
This study examines the effect of liquidity management on bank’s performance in Nigeria from the period 1980-2017. The major aim of the study was to find empirical evidence of degree to which effective liquidity management affects bank performance and how to improve bank performance and liquidity position. The cointegration and error correction technique were produced from the ARDL technique of data analysis as well as Granger causality test was employed to investigate the relationship between liquidity management and banks’ performance. The study reveals that there is a long run relationship between banks’ performance and the selected key variables, although LQR was found to be the only significant variable in the model from the individual test, however, it was jointly shown that the liquidity components significantly impact on banks’ performance in Nigeria in the long run. Based on the empirical findings, we recommend that central bank of Nigeria should ensure effectiveness and efficiency in the review and monitoring of liquidity policy tools in banks in order to stabilize deposit money banks performance and strengthen the financial sector of the economy.